Enhancement of Immunoregulatory Function of Modified Bone Marrow Mesenchymal Stem Cells by Targeting SOCS1. (8th May 2018) - Zhang, Xiaoming; Hua, Fei; Yang, Ziying; Chen, Yueqiu; Teng, Xiaomei; Huang, Haoyue; Zhao, Yunfeng; Shen, Zhenya
Abstract : Objective . The study aim to investigate the role of microRNA-155 (miR-155) on the immunoregulatory function of bone marrow mesenchymal stem cells (MSCs). Methods . MSCs were isolated from 2-week-old Sprague-Dawley rats and identified by flow cytometry using anti-CD29, anti-CD44, anti-CD34, and anti-CD45 antibodies. MSCs were transfected with miR155-mimics, miR155-inhibitor, and control oligos, respectively, and then cocultured with spleen mononuclear cells (SMCs). The mRNA levels of Th1, Th2, Th17, and Treg cell-specific transcription factors (Tbx21, Gata3, Rorc, and Foxp3, resp.) and the miR-155 target gene SOCS1 were detected by quantitative real-time PCR (qPCR) in SMCs. The proportion of CD4 + FOXP3 + Treg cells was detected by flow cytometry. In addition, the effects of MSCs transfected with miR-155 on the migration of rat SMCs were investigated by transwell chamber. Results . CD29 and CD44 were expressed in MSCs, while CD34 and CD45 were negative. The percentage of CD4 + FOXP3 + Treg cells in the SMC population was significantly higher compared with that noted in SMCs control group (p < 0.001 ) following 72 hours of coculture with miR155-mimics-transfected SMCs. In contrast, the percentage of CD4 + FOXP3 + Treg cells in the SMCs cocultured with miR155-inhibitor-transfected MSCs was significantly lower compared with that noted in SMCs control group (p < 0.001 ). MiR155-mimics-transfected MSCs inhibited the expression of Tbx21, Rorc, and SOCS1, while the expression of Gata3 and Foxp3 was increased. In contrast to the downregulation of the aforementioned genes, miR155-inhibitor-transfected MSCs resulted in upregulation of Tbx21, Rorc, and SOCS1 expression levels and inhibition of Gata3 and Foxp3 . In the transwell assay, miR155-mimics-transfected MSCs exhibited lower levels of SMCs migration, while the miR155-inhibitor-transfected MSCs demonstrated significantly higher levels of migration, compared with the blank control group (p < 0.01, resp.). Conclusion . miR-155 favors the differentiation of T cells into Th2 and Treg cells in MSCs, while it inhibits the differentiation to Th1 and Th17 cells.